Public school teachers’ perceptions of students’ diversity, cultural, and linguistic needs in the United States - Zamani Roodsari, Sedighe (English Language Teaching Educational Journal, 2023)
The need for culturally and linguistically sustaining teaching has become more apparent as school communities across the United States continually grow in cultural and linguistic diversity. This study investigated equity-based instruction for Culturally and Linguistically Diverse (CLD) students by examining public school teachers’ perceptions of preparation for diversity and inclusion of CLD students. A CLD research-based survey was designed and administered to 200 elementary and secondary school teachers in ten public schools in the United States. The study examined teachers’ perceptions, attitudes, self-awareness, and preparation toward CLD students’ cultural and linguistic needs. The analysis of the data uncovered evidence related to the themes of CLD instructional awareness and preparation in participants regarding their gender, race, age, ESL experience, highest degree, and years of teaching. The major findings of the study revealed the role of CLD-related training and awareness on the effectiveness of teacher preparation and their perceptions of the diversity of the students. The study concluded by providing implications for teachers, schools, educators, and policymakers on providing an equity-based educational environment for all students including the CLD ones.